Ear nose throat manifestation of tuberculosis: a retrospective study in a tertiary care health centre of North India - Gupta, Sucheta; Gupta, Vinod (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Tuberculosis (TB) involving organs other than the lungs is termed as ’extra pulmonary TB’. Very few studies on otorhinolaryngeal manifestations of TB have been conducted. The aim of this study was to find out incidence of head and neck TB, its varied presentations and clinical manifestations and its association to risk factors such as smoking and alcohol consumption. Methods: A retrospective randomized observational study was conducted in the department of otorhinolaryngology and head neck surgery, CHC, Chenani, Udhampur, on 120 patients, diagnosed with extra pulmonary TB in ear, nose and throat region of 11 and above age group, over a period of eight months and a follow-up of 6 months. Results: Out of the 120 selected for the study, majority belonged to the 36-60 years age group (56.67%). Most of the patients were males (57.5%). TB lymphadenopathy was found to be the most common lesion (84.17%), followed by laryngeal TB (6.67%). There were multiple matted lymph nodes in 69 cases and single lymph node in 8 cases; bilateral lymph node involvement was noted in 38 cases. Fever and swelling in the neck were most common presentations. No association was found between specific TB lesions and Smoking or alcohol consumption. 55% of patients showed no co-existing illness. FNAC was the principal diagnostic investigation for the lymph node TB. Conclusions: Changing patterns of presentations of laryngeal, aural and nasal TB was observed in the study. Therefore, otorhinolaryngologists must keep TB in mind while dealing with head and neck lesions.